Who gets in? a conjoint analysis of labour market demand and immigration preferences in England and Japan. - Kawakami, Riku; Scotto, Thomas J.; Dorussen, Han; Pickering, Steve; Reifler, Jason; Sunahara, Yosuke; Tago, Atsushi; Yen, Dorothy (Journal of Ethnic & Migration Studies, 2026)
We advance research on attitudes towards immigration using an experimental design that more clearly separates between skill level and labour market demand. In single profile conjoint design experiments fielded in England and Japan, we replicate the well-established finding that high-skill immigrants are generally preferred to low-skill immigrants. However, we also show a more nuanced result in that labour market demand – regardless of skill level – is also important. Indeed, in both England and Japan, the public is willing to accept low-skill workers in high-demand occupations at levels at least as much as for high-skill but low-demand occupations. Labour market demand is an important factor in understanding attitudes towards economic migration.